Kultura narodowa w rubrykach. Charakterystyka porównawcza polskich i brytyjskich dzienników ogólnokrajowych - Zięba, Anna; Borowiak-Dostatnia, Marta (Acta Universitatis Lodziensis. Folia Linguistica, 2012)
The objective of this paper is to examine the section structure of two national dailies, namely The Guardian and Gazeta Wyborcza with content analysis tools. The differences are then studied in the context of national cultures characterized within the framework of Hofstede’s dimensions of culture and Hall’s low-context and high-context societies. Thereby, we investigate the relationship between national culture and communication patterns occurring in the press to conclude that a national culture has major impact on the overall structure of the dailies, as well as on the length of individual sections and the number of special reports.